MASALAH PEMILIHAN PERSONAL DIGITAL ASSISTANT (PDA) (Suatu Pendekatan dengan Metode Data Envelopment Analysis (DEA)) - Sani Susanto; F. Rian Pratikto (Majalah Ilmiah Ekonomi Komputer, 2005)
Twelve types of Personal Digital Assistant (PDA), the features and prices of each are known, are currently available in the market. An efficient PDA is defined the one with appropriate features for its current price. The Data Envelopment Analysis (DEA) is applied to determine whether certain PDA is efficient.Keywords: Data Envelopment Analysis, Efficiency